(untitled) (Biological Sciences - PJSIR, 2005)
Studies were conducted to develop and release new improved wheat (Triticum aestivum L) varieties that can yield better and resist the diseases. On the basis of performance under field conditions, a line, MLT’S’ (Metaltail)= ORE F1 158/FDI/Kl/BB/3/Nac, was selected from the Bread Wheat Observation Nursery MRA (1985-86), received through the courtesy of CIMMYT (Mexico) and given the No. V-7222. This line was tested/evaluated in 36 yield trials at different locations in Preliminary and Advanced Yield Trials (1986-89), Micro Wheat Yield Trials (1989-90) and National Uni- form Wheat Yield Trials (1990-91 and 1991-92). On the average of 36 yield trials, Bahawalpur-97 gave 2.14, 5.94 and 1.22% higher yield than Inq-91, Pwz-94 and Pb-96, respectively. Its production technology was also developed. Its best sowing time was November to December. It gave maximum yield when NPK @ 125-100-50 kg/ha was applied. It was resistant to all foliar diseases. Its yield potential was 7200 kg/ha. This variety was approved and released by the Punjab Seed Council, Lahore, as a general-purpose variety for Southern Punjab in the name of “Bahawalpur-97” during 1998.